2022
DOI: 10.3389/feduc.2022.820321
|View full text |Cite
|
Sign up to set email alerts
|

Does Instructional Quality Impact Male and Female University Students Differently? Focusing on Academic Stress, Academic Satisfaction, and Mental Health Impairment

Abstract: Gender differences in university students’ well-being and mental health are prominent concerns in higher education. During the COVID-19 pandemic, male and female students have reported specific stressors that have impacted their well-being and mental health, including difficulty concentrating, concerns about academic performance, and classroom workload. All of these stressors could be mitigated by instructional quality in courses. This study sought to better understand the associations between instructional qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Previous studies have focused on the relationship between campus green spaces and college students’ mental health [ 6 , 15 , 31 , 32 , 33 , 34 ] and the relationship between academic achievement and mental health [ 8 , 35 , 36 ]. However, few studies have used academic achievement as a mediating variable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on the relationship between campus green spaces and college students’ mental health [ 6 , 15 , 31 , 32 , 33 , 34 ] and the relationship between academic achievement and mental health [ 8 , 35 , 36 ]. However, few studies have used academic achievement as a mediating variable.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the pandemic on the decline in student mental health is due to economic pressure, fear of exposure to the virus [70], decreased attention from parents due to inhibition of interaction and communication [52], and decline in physiological health due to lack of quality sleep [47]. From a sample of 209 students, 68% female, 82% freshmen, 50% Asian, 32% Hispanic, 13% white, and 5% other from a public university in Southern California, USA, it was found that declining mental health included concentration difficulties, academic performance concerns and increased task load [32].…”
Section: Student Mental Healthmentioning
confidence: 99%
“…Multiple theoreticians argue that instructional behaviors and instructional quality indirectly affect student achievement emotions 5 through students' competence beliefs 6 and value beliefs 7 (e.g., expectancy-value theory, Eccles et al, 1983;control-value theory, Pekrun, 2006). Multiple scholars have investigated the direct impact of instructional quality on students' motivational beliefs, achievement emotions and performance in school and higher education (Fauth et al, 2014;Dorfner et al, 2018;Rubach et al, 2022). However, scholars also claim that teachers need to create learning environments with different learning opportunities for heterogeneous student needs within their classes.…”
Section: Does Instructional Quality Need To Fit Heterogeneous Student...mentioning
confidence: 99%
“…Heterogeneous preconditions and needs are defined by demographic characteristics (e. g., students' socio-economic status, ethnicity/race, gender, age), functional skills (e. g., abilities, cognitive or behavioral disorders), and academic attitudes (e. g., subject-related motivation, Hamre & Pianta, 2005;Vock & Gronostaj, 2017). Previous studies have focused on the association between the extent of instructional quality and students' academic development explained by demographic and functional risk factors (Rubach et al, 2022;Fauth et al, 2014;Wenger et al, 2020). However, to our knowledge, few scholars have investigated whether the extent of instructional quality is associated with students' academic development by considering the extent to which instructional strategies meet students' need for instructional quality.…”
Section: Does Instructional Quality Need To Fit Heterogeneous Student...mentioning
confidence: 99%
See 1 more Smart Citation